Original articlePituitary metastases from the oncocytic variant of follicular thyroid carcinoma: a case report and diagnostic dilemmas - Matyja, Ewa; Zieliński, Grzegorz; Witek, Przemysław; Kamiński, Grzegorz; Grajkowska, Wiesława; Maksymowicz, Maria (Folia Neuropathologica, 2013)
Metastases to the pituitary gland and sella turcica are uncommon. The distinction between primary and secondary metastatic pituitary tumours is challenging as carcinomas from distant sites might closely resemble, both clinically and histopathologically, non-functional adenomas or primary pituitary carcinomas. Among metastases to pituitary gland ones from thyroid carcinoma are extremely rare. We present a unique case of a 53-year-old male patient with a past history of thyroid carcinoma who underwent repeated surgeries over a period of 7 years for a sellar-parasellar mass with paranasal sinus involvement. Morphologically, the tumour was composed of solid sheaths of monomorphic cells exhibiting oncocytic features. In electron microscope images, the cytoplasm of tumour cells was filled with numerous mitochondria. The tumour was negative for pituitary hormones but exhibited immunoreactivity for cytokeratin AE1/AE3, thyroglobulin and thyroid transcription factor 1 (TTF-1). Based on the clinical data and immunophenotypic profile, the tumour was finally diagnosed as an oncocytic variant of follicular thyroid carcinoma. To our knowledge, this is probably the first report of such peculiar histopathological variant of follicular thyroid carcinoma metastasizing to the pituitary gland. The diagnostic dilemmas considering oncocytic features of the presented case are discussed.